The role of transnational corporations in the Chinese science and technology network - Hennemann, Stefan (ERDKUNDE, 2011)
Cooperation in knowledge creation processes in China is becoming increasingly diverse. Transnational corporations (TNCs) play a crucial role in innovation and the dissemination of new ideas. They are sought-after cooperation partners for an entire set of other actors (e.g., domestic firms and universities), as they are capable of bringing in the most recent knowledge from abroad. However, it is assumed that they rarely work with domestic public research organisations or universities. Following comprehensive reforms of the science and technology system (S&T) in China and strategic changes in the global TNC organisation, public institutions are more likely to serve as potential cooperation partners in creating new knowledge not only for Chinese companies, but also for TNCs. Therefore, a new variety of exchange processes can be expected, with TNCs occupying a prominent position in the knowledge creation system in China. This paper will analyse the network topology and the position of international firms for the creation of research-oriented knowledge in China’s S&T-system. Co-authored publications serve as a proxy indicator for cooperation and knowledge exchange. Between 2003 and 2007, more than 6,000 articles were co-authored with employees of companies in China. These data have been used to create a network that will be analysed using state-of-the-art network science methods. This analysis thus offers a unique insight into the role of TNCs for the Chinese scientific knowledge network.